Work situation awareness, incidence of accidents and severity & job satisfaction in the construction industry - Harun, Nurhaniza (Pusat Pengajian Sains Kesihatan, 2014)
Construction industry is among the most hazardous, as measured by work-related mortality, injury rates, and workers' compensation payments. The main objective of this study was to investigate and identify the present status of work situation awareness, incidence of accidents and severity, and job satisfaction among the general workers at the construction site. The correlation between these factors with socio demographic data was evaluated. The study was conducted from December 2013 to March 2014. The methodology adopted in this study was based in comprehensive questionnaire targeting 369 general workers of construction site. Their preference was rated using a 5-point Likert scale ranging from very disagree to highly agree. The questionnaire set is a combination of Work Situation Awareness Scale, Incidence of Accidents Severity Survey and Job Satisfaction Survey. It was found that construction workers showed an average mean of work situation awareness. There was no significant impact of socio demographic on the awareness. In contrast, the construction workers recorded a higher mean of identification of accidents’ severity and job satisfaction. There was no significant impact of socio demographic on the accidents’ severity, however, there was significance between job satisfaction with the length of service, p<Q.05 with (p=0.014). Result revealed a poor positive correlation significance, p<0.05 between Work Situation Awareness and Job Satisfaction with (/-=0.133). Based on the findings from the study, monitoring and safety enforcement are necessary for effective construction working situation awareness, accident prevention, and job satisfaction of the workers.